Survey the effectiveness of education based on message framing through mobile phone on women's physical activity - Ghodratollah Shakerinejad; Zahra Baji; Masoumeh Tehrani; Farzaneh Jarvandi; Maria Cheraghi; Nasser Hatamzadeh (BMC, 2023)
Abstract Background Physical activity in female employees is a healthy behavior and increases strength, endurance, improves flexibility, improves the feeling of vitality and freshness, improves health, and ultimately increases life expectancy. Health messages are one of the most effective ways to engage people and motivate them to perform healthy behaviors. The purpose of this study was to the study of the effectiveness of education based on message framing through mobile phone (whatsapp) on the physical activity of women employees of universities and higher education institutions in Ahvaz city. Method In this interventional study, 90 of female employees of three universities and higher education institutions of Ahvaz city were selected by random sampling and randomly divided into three groups (30 participants) receiving gain framed messages, receiving loss framed messages and the control group. The tools of data collection were demographic information questionnaire and international physical activity questionnaire (IPAQ). The participants of the intervention groups received educational messages about physical activity behavior in two different gain and loss framed messages through whatsapp for one month. Data were collected from three groups at the beginning of the study, immediately and two months after the intervention, and were analyzed using SPSS version 26. Results The results showed that there was a significant increase in the average physical activity score after the intervention in two interventional groups. by comparing the increase of this score, 53% improvement in physical activity is observed in the gain message group and 15% in loss massage group but there was no significant increase in the control group. Conclusion The results of this study showed that the design and implementation of education programs based on message framing, especially gain framed messages through online education (Whatsapp) can improve and promote physical activity behavior in women employees.